2000
DOI: 10.1523/jneurosci.20-07-02673.2000
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Ionotropic GABA Receptors Mediate Presynaptic and Postsynaptic Inhibition in Retinal Bipolar Cells

Abstract: Ionotropic GABA receptors can mediate presynaptic and postsynaptic inhibition. We assessed the contributions of GABA(A) and GABA(C) receptors to inhibition at the dendrites and axon terminals of ferret retinal bipolar cells by recording currents evoked by focal application of GABA in the retinal slice. Currents elicited at the dendrites were mediated predominantly by GABA(A) receptors, whereas responses evoked at the terminals had GABA(A) and GABA(C) components. The ratio of GABA(C) to GABA(A) (GABA(C):GABA(A)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
87
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 49 publications
18
87
0
Order By: Relevance
“…Previous work has suggested an IPL component to bipolar cell surround responses. recorded lightevoked GABA C receptor-mediated IPSCs in bipolar cells, and subsequent studies demonstrated that depolarization of amacrine cells evoked synaptic GABAergic currents in salamander and ferret bipolar cells (Lukasiewicz and Shields 1998;Shields et al 2000). Here, we extend these findings by showing that blockade of amacrine cell action potentials with TTX reversibly suppressed light-evoked GABAergic IPSCs in bipolar cells.…”
Section: Postsynaptic and Presynaptic Components Of The Ttx-sensitivesupporting
confidence: 70%
“…Previous work has suggested an IPL component to bipolar cell surround responses. recorded lightevoked GABA C receptor-mediated IPSCs in bipolar cells, and subsequent studies demonstrated that depolarization of amacrine cells evoked synaptic GABAergic currents in salamander and ferret bipolar cells (Lukasiewicz and Shields 1998;Shields et al 2000). Here, we extend these findings by showing that blockade of amacrine cell action potentials with TTX reversibly suppressed light-evoked GABAergic IPSCs in bipolar cells.…”
Section: Postsynaptic and Presynaptic Components Of The Ttx-sensitivesupporting
confidence: 70%
“…Although presynaptic GABA receptors with pharmacology consistent with homomeric GABA C receptors have been described in the retina (Matthews et al, 1994;Shields et al, 2000) and superior colliculus Kirischuk et al, 2003), our evidence favors direct activation of -containing receptors in the postsynaptic membrane for several reasons: (1) the presence of the 1 subunit is necessary to elicit responses in DVN and NTS neurons with CACA, consistent with the view that this agonist acts preferentially on subunit containing GABA receptors (Chebib and Johnston, 1999;Zhang et al, 2001), because only neurons that were 1-immunopositive responded to this compound, (2) the actions of CACA persist in the presence of TTX and blockade of excitatory amino acid receptors, as well as when synaptic transmission is blocked in a low Ca 2ϩ -high Mg 2ϩ solution, (3) subunits were also localized postsynaptically using two different antibodies at the ultrastructural level. However, these responses were highly unusual because they were blocked by low concentrations of bicuculline (10 M) as well as the GABA C receptor antagonist TPMPA.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we use wild-type (WT) mice (C57BL/6J strain; The Jackson Laboratory, Bar Harbor, ME) and GABA C 1 null mice that lacked functional GABA C receptors (crossed onto the C57BL/6J background) (McCall et al, 2002). The experimental techniques were similar to those described in our previous studies (Shields et al, 2000;McCall et al, 2002;Eggers and Lukasiewicz, 2006). Briefly, mice were dark-adapted overnight, and all dissection and recording procedures were performed under infrared illumination to preserve the light sensitivity of the preparations.…”
Section: Methodsmentioning
confidence: 99%